2016
DOI: 10.1038/srep37371
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor and Histone deacetylase 6 mediate the differential effect of dexamethasone during osteogenesis of mesenchymal stromal cells (MSCs)

Abstract: Lineage commitment and differentiation of mesenchymal stromal cells (MSCs) into osteoblasts in vitro is enhanced by a potent synthetic form of glucocorticoid (GC), dexamethasone (Dex). Paradoxically, when used chronically in patients, GCs exert negative effects on bone, a phenomenon known as glucocorticoid-induced osteoporosis in clinical practice. The mechanism on how GC differentially affects bone precursor cells to become mature osteoblasts during osteogenesis remains elusive. In this study, the dose and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 61 publications
2
40
1
Order By: Relevance
“…On one hand, Dex increased the expression of RUNX2 and its transcriptional targets, ALP and OSX. On the other hand, Dex significantly downregulated the expression of late osteogenic markers, COL1A1, OPN, OCN, and BSP2 (Subramaniam et al, 1992;Langenbach and Handschel, 2013;Rimando et al, 2016). Therefore, we hypothesized that extended Dex treatment is likely to inhibit osteogenesis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…On one hand, Dex increased the expression of RUNX2 and its transcriptional targets, ALP and OSX. On the other hand, Dex significantly downregulated the expression of late osteogenic markers, COL1A1, OPN, OCN, and BSP2 (Subramaniam et al, 1992;Langenbach and Handschel, 2013;Rimando et al, 2016). Therefore, we hypothesized that extended Dex treatment is likely to inhibit osteogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…To optimize osteogenesis, we tested the supplementation of 1α, 25-dihydroxyvitamin D3 (VitD3) (Lou et al, 2017) and an osteogenic protein BMP7 (Luu et al, 2007). We also examined if the withdrawal of dexamethasone (Dex) at a later stage could enhance osteogenesis (Subramaniam et al, 1992;Rimando et al, 2016). As shown in Figure 2A, five different osteogenic medium compositions were compared: Group 1 (Gr 1), MM (negative control); Gr 2, OM; Gr 3, OM + 10 nM VitD3; Gr 4, OM + 10 nM VitD3 + 100 ng/ml BMP-7; Gr 5, OM + 10 nM VitD3 + 100 ng/ml BMP-7, with Dex treatment only during the first 14 days.…”
Section: Optimization Of Chondrogenic and Osteogenic Differentiation mentioning
confidence: 99%
“…35 Our results could be also explained by the fact that dexamethasone could down regulate the osteogenic markers, such as alkaline phosphatase, osteocalcin, and Runt-related transcription factor 2 (Runx2). 36 Dexamethasone motivates the expression of histone deacetylase 6 (HDAC6) that binds to glucocorticoid receptor and may prevent the osteocalcin expression. 37 Other researchers concluded that dexamethasone could reduce the expression of insulin like growth factors I and II because these growth factors increase osteoblast differentiation, type I collagen synthesis, and bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Inability of Group 3 and 4 scaffolds to induce differentiation may be attributed to very high concentrations of DEX released. The optimum concentration of DEX needed to induce the osteogenic differentiation is 10-7 [49][50][51]. In the CPC discs doped with DEX, DEX may have been eluted in excess and thus had an inhibitory effect.…”
Section: Alkaline Phosphatase Activitymentioning
confidence: 99%